KUALITAS LAYANAN SISTEM INFORMASI PENGARSIPAN MENGGUNAKAN METOE SERVQUAL - rice Novita (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
Bank Indonesia - Records Management System (BI-RMS) is a web-based Bank Indonesia archive management service. This system began operating in early 2012 at the Bank Indonesia Head Office. Then in mid-2013, the BI-RMS system began operating at KPw Bank Indonesia, Riau Province. With various features offered in the BI-RMS, of course, it will simplify the management of records. However, there are only a few employees at KPw Bank Indonesia in Riau Province who use BI-RMS. Even though every employee can access the BI-RMS, only a few people often use the system. Even the system is more often used by apprentice employees than permanent employees. Therefore, a system analysis is needed to determine the quality of system services using the Service Quality (ServQual) method. The results of the analysis are in the form of ServQual gap analysis and service quality level per ServQual dimension. The results of this analysis are expected to solve the problems that exist in the system